ECOLOGICAL-GEOGRAPHICAL CONDITIONALITY AND PROGNOSIS DISEASE OF CANCER OF THE CHILDREN'S POPULATION OF DAGHESTAN REPUBLIC - G. M. Abdurakhmanov; M. G. Daudova; A. G. Gasangadzhieva; P. I. Gabibova; E. G. Abdurakhmanova (Юг России: экология, развитие)
For the first time in the study area carried out a comprehensive statistical analysis of child cancer rates in the period from 1991 to 2010 and its forecast for the next 10 years. Determined the dynamics and the predominant forms of locali-zation of child cancer.Also calculated the age structure of morbidity by malignant neoplasms of the child population of Dagestan.